Relative Impact of Climate Change on Land Value Across Agro-Ecological Regimes in Nepal - Budhathoki, Nandakaji; Bhatta, Gopal Datt (Economic Journal of Nepal, 2015)
This study examined the impact of climate change on the value of land across three agro-ecological regions of Nepal by adopting a Ricardian Analysis of 2748 farms. The study reveals that value of irrigated and non-irrigated farms of the hills and terai regions are significantly affected as compared to that of mountain region. Seasonal temperatures affect land value of irrigated lands more than non-irrigated ones. The increment in precipitation and temperature has severe impact on both irrigated and non-irrigated land across different agro-ecological zones and severity is more on value of irrigated land of Terai region.Since value of land is highly dependent on quality and productivity of land, the focus should be given to reduce climate change impact on agricultural productivity through potent climate smart adaptive interventions. More pilot research needs to be done in different agro-ecological conditions to single out such interventions in order to make farming systems more resilient amid climate change scenario. The Economic Journal of Nepal, Vol. 35, No. 2, April-June 2012 (Issue N0. 138)